Teacher education in the wake of Covid-19 : ISATT 40th anniversary yearbook - Craig, Cheryl J.; Mena, Juanjo; Kane, Ruth G. (Advances in research on teaching ;, 2023)
Research on teacher education and classroom teaching has evolved significantly in recent decades, with more scholarship taking an international and/or other intersectional lenses. The International Study Association on Teachers and Teaching (ISATT) has changed with the field. Beginning as a predominantly white European and North American organization in 1983, it now has active membership from more than 60 countries across the globe. The ISATT 40th Anniversary Yearbook, comprised of four volumes, reflects this growth through celebrating the contributions of ISATT members over time and offering current scholarly research to inform current and future teacher education and teaching. This volume, Teacher Education in the Wake of Covid-19, pays particular attention to ways in which teaching and teacher education have been impacted by, and responded to, advances in technology and to the coronavirus pandemic. The editors present chapters dedicated to examining the tools of technology and their impact within teaching and teacher education as we look toward the future possibilities. The chapters analyze the lived reality of pivoting to embrace pandemic pedagogogies; the pandemic and social relationships; assessment during the pandemic; and the consequences for equity and agency. They also examine the tools of technology and future possibilities as well as how technology unavoidably became a part of the global teaching and teacher education pandemic response. All four volumes making up the 40th Anniversary Yearbook offer invaluable insights for teacher educators and educational researchers the world over, offering international perspectives from North America, Europe, South America, Asia, Africa, and Australasia.